Translation in Fashion and the art of dressing - Laylo Khaydarova; Norova Sarvinoz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This paper discusses the theoretical and methodological issues of translating fashion words and expressions and compares these with the expectations and perceptions of students. Results indicate that when analyzing the translation of the fashionable terminology of glossy magazines, it is noticed that for most of the terms translators do not find equivalents in Russian and use tracing and transcription, especially for shoe designs. It is assumed that it is for this sense of communication in global simplicity. We can conclude that a large layer of vocabulary is translated by tracing, transliteration of transcription in the absence of an equivalent in the target language.